Pengaruh Variasi Konsentrasi Asam dan Variasi Pengendap pada Sintesis Besi Oksida dari Limbah Karat Besi - Asiyah Nurrahmajanti; Anisya Lisdiana (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Iron commodities are one of the very important commodities and are used in various sectors. The supply of iron and its derivatives has so far relied solely on mining results. However, the impact of mining results can be detrimental from geological, environmental, and health perspectives. One potential that is often overlooked is iron rust waste. The synthesis of iron oxide pigments from iron rust waste can be done using the precipitation method with variations of 1M and 4M HCl concentration and variations of the precipitant NH4OH 4M and NaOH 4M. The synthesized iron oxide shows red solids for the NaOH precipitant variation and blackish-red for the NH4OH precipitant. EDS results indicate that the NH4OH precipitant generates purer iron oxide pigments compared to NaOH. In the SEM testing, it was observed that iron oxide was successfully synthesized with a crystalline phase, namely the formation of rhombohedral crystals in the HEM2 and HEM4 variation, as evidenced by XRD testing showing 11 peaks at 2θ(º) 24.2; 33.3; 35.6; 41; 49.6; 54.2; 57.7; 62.5; 64.1; 69.7; and 72.1 compared to JCPDS 33-0664.